2010
DOI: 10.1148/radiol.09090690
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Current Guidelines, and Their Evidence Base, on Risk of Lactic Acidosis after Administration of Contrast Medium for Patients Receiving Metformin

Abstract: , MBBS, MSc (Public Health), FAFPHM Purpose:To systematically review evidence about the relationship between metformin administration and the use of iodinated contrast medium and risk of lactic acidosis (LA) and to assess the quality of fi ve current guidelines for use of contrast medium in patients who are taking metformin. Materials and Methods:A search strategy was developed by using search terms related to metformin, contrast media, and LA. Searches were conducted in MEDLINE (Ovid), all Evidence-based Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(41 citation statements)
references
References 17 publications
0
34
0
7
Order By: Relevance
“…However, there is much disagreement as to the appropriate schedule to follow. 16 The Royal Australian and New…”
Section: Articlementioning
confidence: 99%
“…However, there is much disagreement as to the appropriate schedule to follow. 16 The Royal Australian and New…”
Section: Articlementioning
confidence: 99%
“…5 A meta-analysis of randomized trial showed that metformin reduced adverse cardiovascular events (MI, stroke, peripheral artery disease and cardiovascular death) versus placebo/no therapy. 16 A non-significant trend towards reduced allcause mortality was also noted with metformin monotherapy. 16,17 This benefit may be especially pronounced in obese patients with a systematic review trial reporting a reduction in all-cause mortality with metformin in this population when compared with sulfonylurea.…”
Section: Cardiovascular Safetymentioning
confidence: 98%
“…16 A non-significant trend towards reduced allcause mortality was also noted with metformin monotherapy. 16,17 This benefit may be especially pronounced in obese patients with a systematic review trial reporting a reduction in all-cause mortality with metformin in this population when compared with sulfonylurea. [17][18][19][20][21][22] A systematic review of cohort studies found no increased risk for cardiovascular morbidity and mortality with metformin use across various subgroups of patients compared with placebo or insulin.…”
Section: Cardiovascular Safetymentioning
confidence: 98%
“…Although the recommended measures vary among guidelines, most guideline documents do not recommend the suspension of biguanides in patients with normal kidney function before the use of iodinated contrast media [29][30][31] ( Table 2). …”
Section: Rationale Cq3-5mentioning
confidence: 99%